DAKWAH KONTEMPORER DALAM MERESPON SITUASI PANDEMI COVID-19 - Hikmi Rahmiati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
The Covid-19 pandemic has caused instability in the order of people's lives, including in preaching activities. Da'wah which is usually done by gathering and crowding is becoming increasingly limited, the preachers are required to innovate in each of their da'wah activities. One of the da'wah models that can be used to respond effectively and efficiently to space, time and cost during the Covid-19 pandemic is the contemporary da'wah model. Researchers took two figures, namely Sokhi Huda and Fahrurrozi to explain the concept of contemporary da'wah. The research method uses a descriptive qualitative approach with a library research strategy. The results of this study are: the quality of contemporary preachers who interpret da'wah as a mandate from God with all the accompanying situations and conditions, contemporary da'wah material is interpreted as a combination of religious messages and health messages, and contemporary da'wah media is defined as massive use of virtual space